ANALISIS USAHATANI KEDELAI PADA PROGRAM GERAKAN PENERAPAN PENGELOLAAN TANAMAN TERPADU (GP-PTT) DI ABUPATEN GUNUNGKIDUL - Raras Arumingsari Manuhoro; Vandrias Dewantoro; Nanik Dara Senjawati (Jurnal Dinamika Sosial Ekonomi, 2017)
This research was a purpose to review an compare soybean production, business efficiency and business benefits of following the movement program GPPTT and non GPPT in the Gunung Kidul district. The research method used in this research is descriptive method. Methods of implementation of the research is survey method. Method of determining location using multistage sampling method. Sampling methods farmer groups of respondens in this research use simple random sampling. Methods of sampling respondents use census method. The data used are primary data and secondary data. The analysis method using ttes and independent t-test. Results from this research is the average production of farming program GPPTT is 1389,31 kg/ha/th and non GPPTT is 1366,67 kg/ha/th. The value of profit farming soybeans gained from GPPTT program is Rp 6.194.119,02/ha.th, and for non GPPTT program is Rp 5.779.111,53/ha/th. In this research the increamentalsoybean benefits cost ratio between GPPTT program and non GPPTT programobtained result are 18,48. Keywords: soybean farming, GPPTT program